Digital-Biotechnology: A Framework of Bioinformatics used Mobile-Health Technologies in Nigeria-Universities 5G-Readiness Deployment-Plan - Birnin-Kudu, Abdullahi; Awang, Hapini; Sheik Osman, Wan Rozaini (Emerging Advances in Integrated Technology, 2022)
Digital Bioinformatics Innovation Initiative (DBII) is a branch of science that used Information and Communication Technologies (ICTs), government electronic services such as electronic government (e-government), electronic health (e-health), and mobile technologies (mobile health) to examine knowledge and information. DBII can also use Internet services or Fourth Generation (4G), and Fifth Generation (5G) services for its deployment and implementation opportunities in developing nations health and healthcare system and other domains. Some of the current digital bioinformatics processes are geometadata profiling, use of mobile technologies (mobile phones) and Artificial Intelligence (AI) in various 5G readiness deployment fields. Despite the benefits of this novel digital innovation, its deployment and implementation have been affected by poverty, lack of enough routine anticipation and determination, initial understanding of mobile phone, inadequate of research funding, personal innovativeness, lack of stable and dependable research methodologies. At present, there is limited number of research that highlighted these aspects to fill in research gaps and find alternative solution to DBII research problems. Therefore, a pilot survey was conducted among professionals in various fields who are knowledgeable about DBII from February 20th, 2020, to January 1st, 2022. Eight academic research professionals, and fifteen health and healthcare workers validated 6 behavior intention factors. Similarly, six hundred postgraduate and undergraduate students, health and healthcare specialists and other professionals across six Nigerian geographical zones participated in pilot survey using the proposed Precaution Adoption Model Process (PAMP) Mobile health questionnaire. Under this situation Principal Component Analysis (PCA) pre-processed online geometadata profiles, experts confirmed behavior intention items towards hypothesis generation, hypothesis testing, and development of digital bioinformatics framework of to use mobile phones in Nigeria Universities 5G readiness deployment plan. The study has discussed several theoretical and practical implications of digital bioinformatics for system designers and developers.